Oral candidiasis - Perleche Mimicking Malignancy (Community Based Medical Journal, 2014)
Candida species inhabit the mucosal surfaces of healthy individuals. Major forms of oral candidiasis are pseudomembranous and atrophic form, but chronic hyperplastic candidiasis (CHC) is rarely seen. We encountered a case of whitish plaque with nodule and ulceration. When an intraoral nodule is observed, the possibility of CHC should be taken into consideration. Biopsy of the lesion failed to show any signs of malignancy, and patient responded well to oral fluconazole therapy only.CBMJ 2014 January: Vol. 03 No. 01 P: 53-55